The Cross-Entropy Method and its Application to Minimize the Ripple of the Magnetic levitating Forces of a Maglev System - Yang, Shiyou; Bai, Yanan; Machado, Jose Marcio [UNESP]; Chen, Z. M.; Jiang, J.; Ma, X (Japan Society Applied Electromagnetics & Mechanics, 2009)
The Cross-Entropy (CE) method is developed and applied to minimize the ripple of the magnetic levitating forces of a maglev system with promising results.